Implementation of medication review type 2a in community pharmacies: a longitudinal survey study - Tobback, Eline; De Wulf, Isabelle; Wauters, Ella; Mendez Santos, Delia; Patris, Stéphanie; Dalleur, Olivia; Tommelein, Eline; Foulon, Veerle; Philippe, Geneviève; De Vriese, Carine; Steurbaut, Stephane; Duquet, Nathalie; et al. (Frontiers in Pharmacology, 2025)
IntroductionMedication Review Type 2a (MR2a), introduced to enhance medication use and health outcomes, has been reimbursed in Belgian community pharmacies since April 2023; however, its implementation status remains unreported.AimThis longitudinal survey study aimed to document MR2a implementation among community pharmacists by identifying both facilitating and hindering factors.MethodsA bilingual online survey was distributed quarterly from October 2023 to October 2024 to all Belgian community pharmacies. The 45-item questionnaire—featuring multiple-choice, Likert scale, and open-ended questions—captured pharmacists’ experiences about MR2a.ResultsAcross all rounds (n = 708), consistent findings emerged regarding key barriers and facilitators to MR2a implementation. Major challenges included time limitations, privacy-compliant communication systems, personnel shortages, inadequate consultation spaces and poor collaboration with general practitioners. Training and patient engagement were identified as key facilitators, yet ongoing stakeholder support was considered essential to ensure successful MR2a implementation.ConclusionRepeated surveys offer timely insights into MR2a implementation in community pharmacies. The slow progress confirms existing obstacles and stresses the importance of continued support and improved interprofessional collaborations. These insights are expected to inform MR implementation locally and internationally.